Familial hypercholesterolemia: experience from France. Issue 2 (April 2018) - Rabès, Jean-Pierre; Béliard, Sophie; Carrié, Alain
Abstract : Purpose of review: We provide an overview of molecular diagnosis for familial hypercholesterolemia in France including descriptions of the mutational spectrum, polygenic susceptibility and perspectives for improvement in familial hypercholesterolemia diagnosis. Recent findings: Molecular testing for familial hypercholesterolemia is recommended for patients with a LDL-cholesterol level above 190 mg/dl (adults) associated with criteria related to personal and family history of hypercholesterolemia and premature cardiovascular disease. Among the 3381 index cases included with these characteristics in the French registry for familial hypercholesterolemia, 2054 underwent molecular diagnosis and 1150 (56%) were found to have mutations (93.5% in LDL Receptor ( LDLR ), 4.7% in apolipoprotein B and 1.8% in Proprotein convertase subtilisin/kexin type 9 ). A total of 416 different pathogenic variants were found in the LDLR gene. Based on gene score calculation, a polygenic origin may be suggested in 36% of nonmutated patients. Involvement of genetic counselors and education of healthcare professionals for genetics of familial hypercholesterolemia are underway with the aim of improving the efficiency of the diagnosis. Summary: Genetic cascade screening for familial hypercholesterolemia is currently implemented in France with the complexity to address the diversity of its molecular cause in index cases. Optimization of patient care pathways is critical to improve both the rate of diagnosis and the management of familial hypercholesterolemia patients.